The Revolutionary Samuel Adams - Schiff, Stacy (Little, Brown & Company, 2022)
Thomas Jefferson once asserted that "for depth of purpose, zeal, and sagacity, no man in Congress exceeded, if any equaled, Sam Adams." John Adams called him "the most elegant writer, the most sagacious politician, and celebrated patriot perhaps of all." But in spite of his celebrated status among America's founding fathers as a revolutionary leader, Samuel Adams' life and achievements have been largely overshadowed in the history books.
Keywords: Revolutionary